Epidemiological Patterns of Gastrointestinal Parasitic Infections in Equine Populations from Urumqi and Ili, Xinjiang, China - Yabin Lu; Penghui Ru; Sinan Qin; Yukun Zhang; Enning Fu; Mingyue Cai; Nuermaimaiti Tuohuti; Hui Wu; Yi Zhang; Yang Zhang (Veterinary Sciences, 2025)
Gastrointestinal parasitic diseases pose significant health risks to equine populations. This study investigated the epidemiological patterns of equine gastrointestinal parasites in Xinjiang by analyzing 83 fecal samples collected from Ili (n = 62) and Urumqi (n = 21) between August and November 2024. The modified McMaster technique was employed to quantify fecal egg counts (EPG) and was complemented by morphological identification to assess infection dynamics related to geography, breed specificity, and management practices. The results demonstrated an overall infection prevalence of 66.3% (55/83), with strongyles, Parascaris equorum, and Eimeria oocysts being present. Significant geographical variation was observed, with Ili exhibiting a higher prevalence (74.2%) compared to Urumqi (42.9%). Breed susceptibility analysis revealed that there was a 94.1% prevalence in Yili horses versus 42.9% in Kazakh horses. Pasture-managed herds showed markedly higher infection rates (94.1%) than stable-based systems (50.0%). Parasite community composition was dominated by strongyles (82.1%), followed by Triodontophorus spp. (27.7%) and P. equorum (2.4%). These findings highlight severe parasitic infection risks in Xinjiang’s grazing equids, underscoring the urgency of implementing targeted anthelmintic protocols to mitigate disease transmission.